Sperm associated antigen 9 (SPAG9) a promising therapeutic target of ovarian carcinoma. Issue 5 (May 2018) - Jagadish, Nirmala; Fatima, Rukhsar; Sharma, Aditi; Devi, Sonika; Suri, Vitusha; Kumar, Vikash; Suri, Anil
SPAG9 is a novel tumor associated antigen, expressed in variety of malignancies. However, its role in ovarian cancer remains unexplored. SPAG9 expression was validated in ovarian cancer cells by real time PCR and Western blot. SPAG9 involvement in cell cycle, DNA damage, apoptosis, paclitaxel sensitivity and epithelial- mesenchymal transition (EMT) was investigated employing RNA interference approach. Combinatorial effect of SPAG9 ablation and paclitaxel treatment was evaluated in in vitro . Quantitative PCR and Western blot analysis revealed SPAG9 expression in A10, SKOV-3 and Caov3 compared to normal ovarian epithelial cells. SPAG9 ablation resulted in reduced cellular proliferation, colony forming ability and enhanced cytotoxicity of chemotherapeutic agent paclitaxel. Effect of ablation of SPAG9 on cell cycle revealed S phase arrest and showed decreased expression of CDK1, CDK2, CDK4, CDK6, cyclin B1, cyclin D1, cyclin E and increased expression of tumor suppressor p21. Ablation of SPAG9 also resulted in increased apoptosis with increased expression of various pro- apoptotic molecules including BAD, BID, PUMA, caspase 3, caspase 7, caspase 8 and cytochrome C. Decreased expression of mesenchymal markers and increased expression of epithelial markers was found in SPAG9 ablated cells. Combinatorial effect of SPAG9 ablation and paclitaxel treatment was evaluated in in vitro assays which showed that ablation of SPAG9 resulted in increased paclitaxel sensitivity and caused enhanced cell death. In vivo ovarian cancer xenograft studies showed that ablation of SPAG9 resulted in significant reduction in tumor growth. Present study revealed therapeutic potential of SPAG9 in ovarian cancer.